Optimisation of Preheating Temperature for Mechanical Performance of SMAW Welded ASTM A36 Steel - Sumarji Sumarji; Agus Hariyanto; FX. Arif Wahyudianto; Agus Suprihanto (Mechanical Engineering Department - Semarang State Polytechnic, 2026)
The Shielded Metal Arc Welding (SMAW) process applied to ASTM A36 structural steel generates thermal cycles that influence the mechanical behaviour of welded joints. This study investigates the effect of preheating temperature on tensile properties and hardness distribution of SMAW-welded ASTM A36 steel plates with a thickness of 10 mm. Preheating temperatures of none, 150 °C, 250 °C, and 350 °C were applied prior to welding in the 1G position using AWS A5.1 E7016 and E7018 electrodes. Tensile testing was conducted according to ASTM E8, while Vickers hardness measurements were performed across the base metal (BM), heat-affected zone (HAZ), and weld metal (WM). The results show a consistent hardness distribution of WM > HAZ > BM for all preheating conditions, with average hardness values ranging from 190–210 HV in the WM, 179–186 HV in the HAZ, and 164–173 HV in the BM. The yield strength increased from 301.69 MPa (without preheating) to 315.68 MPa at 250 °C, followed by a decrease to 298.70 MPa at 350 °C, which is associated with microstructural softening. In contrast, the ultimate tensile strength remained relatively stable within the range of 443–446 MPa. Based on these results, preheating at 250 °C tends to provide a more homogeneous hardness distribution and higher yield strength, suggesting a more favourable thermal condition for improving the mechanical performance of SMAW-welded ASTM A36 steel. .